ANALISIS KEPUASAN PENUMPANG TERHADAP KUALITAS PELAYANAN TAKSI BLUE BIRD PALEMBANG - ASLAMIA ROSA; DESSY YUNITA (JURNAL MANAJEMEN DAN BISNIS SRIWIJAYA, 2014)
This research was held to reveal how Service Quality influences the Blue Bird Taxi passenger’s satisfactions, the ServQual Dimensions position on Cartesius Diagram, and wheter the linier multi regression result is consistent with those dimensions positions. Using data of 100 respondents, the regression result implies that it is in accord with theServQual Dimensions on Cartesius Diagram of Importance-Performance Analysis/IPA which Tangible and Assurance are on quadrant B. Which it explains the implementations of the services on those dimensions meet the passengers’ expectations. The Reliability is on quadrant A which means the services quality in this dimension should be corrected and improved. The Responsiveness and Empathy are on quadrant C that implies the services quality on these dimensions are good enough although the passenger assumed they are not pretty necessary.